Pengaruh Promosi Kesehatan dengan Media Bukar (Booklet dan Kartu Iva) terhadap Peningkatan Pengetahuan Tentang Kanker Serviks pada Ibu Pus di Puskesmas Kota Mukomuko - Sulastri Sulastri; Murwati Murwati; Emi Pebriani; Meri Efriana Susanti (Universitas Batanghari Jambi, 2023)
Cervical cancer is one of the most common cancers in women worldwide. In Indonesia, cervical cancer ranks second in terms of the number of cancer patients in women but as a cause of death it still ranks first. The purpose of this study was to determine the effect of health promotion using Bukar media (booklets and IVA cards) on increasing knowledge about cervical cancer in women of childbearing age at the Mukomuko City Health Center. The research design used the Pre-Experimental method with the One Group pre-post test design approach. The sample in this study consisted of 24 patients. Accidental sampling was used and the measuring instrument used was a questionnaire sheet. Data analysis used the Paired t test with a significance degree of Î± 0.05. The results of the univariate analysis showed that half of the respondents (50%) had sufficient knowledge before being given health promotion and all respondents (83.3%) had good knowledge after being given health promotion. The results of bivariate analysis showed that there was an effect of health promotion using the open media (Booklet and IVA Card) on increasing knowledge about cervical cancer in women of childbearing age with a p value of 0.003 â‰¤ 0.005. It is hoped that the Mukomuko City Health Center can carry out broader health promotion regarding cervical cancer using other media to increase the knowledge of PUS mothers about cervical cancer and early detection with IVA.